Evidence From a Large Sample on the Effects of Group Size and Decision-Making Time on Performance in a Marketing Simulation Game. (August 2016) - Treen, Emily; Atanasova, Christina; Pitt, Leyland; Johnson, Michael
Marketing instructors using simulation games as a way of inducing some realism into a marketing course are faced with many dilemmas. Two important quandaries are the optimal size of groups and how much of the students' time should ideally be devoted to the game. Using evidence from a very large sample of teams playing a simulation game, the study described here seeks to answer two fundamental questions: What effects on performance does group size have? And, is it possible for groups to spend too much time on decision making? The results indicate that performance increases in line with group size until teams have five members, and then tapers off. Furthermore, performance is shown to rise as time spent on decision making increases, up to a point, after which additional time spent on the game is shown to detract from performance. Implications for marketing instructors are discussed.